2022
DOI: 10.1177/25161032221099979
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver-specific factors and orphanage-context factors contributing to maltreatment of children in institutional care: A multi-level analysis of 24 orphanages in Tanzania

Abstract: Background: High rates of maltreatment and low caregiving quality in institutional care settings have been identified in various low-and middle-income countries. Many studies have focused on children living in institutions. Objective: This study investigates the prevalence of maltreatment, caregiver-specific, orphanage-context factors, and their relation to maltreatment of orphans from the caregivers’ perspective. Participants and setting: In this cross-sectional study, 227 caregivers (67% female) with a mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…Carers in government homes have other factors that might have exposed them to burnout such as more children to care for and a higher number of children with behavioral and emotional problems. Being exposed to long hours of interactions with challenging child behavior (Eastwood & Ecklund, 2008;Savicki, 2002) and work overload (Mkinga et al, 2022) contributes to the residential care workers' risk for burnout.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carers in government homes have other factors that might have exposed them to burnout such as more children to care for and a higher number of children with behavioral and emotional problems. Being exposed to long hours of interactions with challenging child behavior (Eastwood & Ecklund, 2008;Savicki, 2002) and work overload (Mkinga et al, 2022) contributes to the residential care workers' risk for burnout.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies done in assessing caregiver burden at an orphanage in rural South Africa showed approximately 40% of caregivers reported high levels of caregiving burden (Kidman & Thurman, 2014). Poor working conditions such as working under extreme and exhausting conditions of very high caregiver-child ratios and low salaries (Mkinga et al, 2022) may contribute to the development of burden.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The role of the Orphanage is so great for the survival of children who are neglected or do not get care or love from their own parents. So, some researchers are interested in researching orphanages from various perspectives (Mkinga, 2022).…”
Section: Pendahuluanmentioning
confidence: 99%